Primary or Secondary Prophylaxis with Voriconazole Compared with Posaconazole for Prevention of Invasive Fungal Infections After Hematopoietic Stem Cell Transplantation. (4th October 2017) - Jansen, Jeffrey W; Pande, Anupam; Romee, Rizwan; Lawrence, Steven J; Powderly, William
Abstract: Background: Invasive fungal infections (IFI) remain a serious complication in hematopoietic stem cell transplantation (HSCT) patients and are associated with increased costs, morbidity, and mortality. Posaconazole (PCZ) and voriconazole (VCZ) are frequently utilized as antifungal prophylaxis in this population. To date, no direct comparison between PCZ and VCZ exists for the prevention of IFI in adult HSCT patients. Methods: A retrospective cohort analysis of HSCT patients aged ≥18 years who received ≥28 continuous days of primary (PPPx) or secondary (SPPx) antifungal prophylaxis with either VCZ or PCZ between February 26, 2003 and September 30, 2015 at Barnes-Jewish Hospital was conducted. Patients who received PPPx or SPPx with both VCZ and PCZ were analyzed following intention to treat of the initial agent received. Patients who received both PPPx and SPPx were included once for both PPPx and SPPx. The primary outcome of interest was development of possible, probable, or proven IFI as defined by EORTC/MSG guidelines. In the SPPx patients, development of IFI was confirmed as a distinct event from primary IFI based on manual chart review and radiographic evidence. Results: Overall, there were 472 patients included; 402 in the VCZ group and 70 in the PCZ group. At baseline, patients in the PCZ group had more graft vs. host disease (GVHD) prior to prophylaxis (27.1% vs. 16.7%, P = 0.04) and were more likely to be on SPPx (60% vs. 41%, P < 0.01). There were 22 and 1 IFI events in the VCZ and PCZ groups, respectively, which corresponded to a crude incidence rate of 0.345 and 0.077 per 1000 person-days of prophylaxis. Figure 1 displays the Cox proportional hazard model which was completed in the backwards stepwise method accounting for gender, transplant type, GVHD prior to prophylaxis, disease remission, and PPPx or SPPX. The hazard ratio for development of IFI while on prophylaxis between VCZ and PCZ was 5.22 (95% CI: 0.69–39.4; P = 0.11) after controlling for PPPx or SPPx. Conclusion: There was not a significant difference between rates of IFI in HSCT patients who received antifungal prophylaxis with VCZ compared with PCZ. Our data trends towards favoring PCZ but is limited by low rates of IFI. Larger, prospective analyses are necessary to confirm our findings. Disclosures: W. Powderly, Merck: Grant Investigator and Scientific Advisor, Consulting fee and Research grant. Gilead: Scientific Advisor, Consulting fee. Astellas: Grant Investigator, Research grant